Web data integration system: approach and case study - Hajmoosaei, A.; Abdul-Kareem, S. (2008)
There are a lot of valuable data on the web that organizations or users can use to improve their decision making process. It is therefore, very important and critical that this information be complete, precise and can be acquired on time. Most web sources provide data in semi-structured form on the internet. The extraction and combination of semi-structured data from different sources on the internet often fails because of syntactic and semantic differences. The access, retrieval and utilization of information from the different web data sources imposes a need for the data to be integrated. Integration of web data is a complex process because of the open, dynamic and heterogeneity nature of web data. The solution to this problem is a web data integration system. External information can be extracted from web sources and utilized for users through a web data integration system. In this paper, we first propose an approach and architecture for web data integration system and then develop a prototype of the proposed system for Malaysian universities.